Analysis of aroma-active compounds in four Chinese dry-cured hams based on GC-O combined with AEDA and frequency detection methods. (January 2022) - Jiang, Shui; Xia, Dong; Wang, Xiaoming; Zhu, Yaozhou; Chen, Gaole; Liu, Yuan
Abstract: Chinese dry-cured hams have become increasingly appreciated by consumers because of their unique flavor characteristics. In this study, the volatile compounds of four Yunnan dry-cured hams (Xuanwei, Nuodeng, Sanchuan, and Saba) were characterized by monolithic material sorptive extraction (MMSE) and GC-MS. A total of 66 volatile compounds were identified, of which aldehydes and alkanes were the most abundant (>76.43%) in all four hams. The PCA result with 71.04% of the variability demonstrated the potential dominant compounds for the different dry-cured hams. The similarities and differences of aroma-active compounds among the different Yunnan dry-cured hams were studied by using gas chromatography-olfactometry (GC-O) combined with aroma extract dilution analysis (AEDA) and frequency detection (FD) methods. The results demonstrated that 3-methylbutanal, hexanal, 2, 6-dimethylpyrazine, 1-octen-3-ol, dimethyl trisulfide, and nonanal were the most important aroma-active compounds in the Yunnan dry-cured hams. This study contributes to a better understanding of odor quality in Chinese dry-cured hams. Graphical abstract: Image 1 Highlights: The aroma-active compounds of four Yunnan dry-cured hams were researched. GC-O/MS combined with MMSE were used to characterize the volatile compounds. The aldehydes, alkanes and alcohols predominated in the extracted volatile compounds. Six main aroma-active compounds were determined by AEDA and frequency detection.